Gambaran Pelaksanaan Surveilans Covid-19 di Puskesmas Kota Bekasi Tahun 2021 - Ajie, Muhammad Wahyu Nugraha; Martini, Martini; Wurjanto, Moh. Arie; Hestiningsih, Retno (Jurnal Riset Kesehatan Masyarakat, 2022)
Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). The current condition of cases of the spread of COVID-19 in Bekasi City is quite under control. Epidemiological surveillance of COVID-19 is one form of effort to prevent and control the spread of this disease. This study aims to observe the implementation of the COVID-19 surveillance system at the Public Health of Bekasi City. This research is a quantitative research with an observational descriptive approach and uses a cross-sectional study design. The research respondents were COVID-19 surveillance officers at the Public Health of Bekasi City. The sample size in this study was calculated using total sampling. Data was collected by filling out online questionnaires and observations. Data analysis was carried out descriptively and compared with ministerial decrees and surveillance guidelines. In this study, it was found that most of the implementation of good COVID-19 surveillance had a greater proportion in the category of respondents in their early teens, male gender, education level graduated from Bachelor of Health, long working period (> 7 years), double duty/ workloads, and inappropriate categories of surveillance attributes. From this study, it can be concluded that : 1) The Bekasi City COVID-19 Surveillance Officer has carried out the surveillance component well, starting from case finding until activities of information dissemination on COVID-19 cases, and 2) Good implementation of COVID-19 surveillance activities in Bekasi City is greater in proportion to public health center with inappropriate surveillance attribute categories.